Riscos associados ao uso de Oxandrolona por mulheres: uma revisão integrativa - Barroso, Macielle Silva (Brasil, 2024)
The increasing use of anabolic androgenic steroids (AAS) represents a public health concern due to the associated risks, both in therapeutic and abusive doses, especially among gym-goers in Brazil. These compounds, structurally similar to testosterone, are sought after by individuals seeking quick physical changes. However, illicit purchases associated with a lack of medical supervision increase health risks. Oxandrolone, used mainly by women due to the perceived lower risk of serious side effects, is used in several medical conditions and for aesthetic purposes, but its safety and possible impacts on female health are still a concern, given the scarce literature on its effects. This study aims to highlight the possible risks and adverse effects arising from the use of oxandrolone by women for esthetic or sporting purposes. This is an integrative review searched in databases such as PubMed, Scielo and Google Scholar. Using inclusion and exclusion criteria, focusing on studies published since 2003. Based on the studies, there are no reports of side effects at therapeutic doses, however, there are risks related to oxandrolone overdose in women. Some articles suggest that oxandrolone is a less hepatotoxic alternative and does not present adverse effects, however, the idea that this substance is free from significant side effects is not unanimous in the scientific literature. Some authors highlight the most common adverse effects associated with prolonged use of oxandrolone how thinning and oily hair, alopecia, deepening of the voice, hair growth, acne on the face and body, bladder irritation, dysregulation of the menstrual cycle, clitoral atrophy, increased libido, changes in mood and loss of feminine characteristics. Furthermore, with abusive use, the adverse effects of oxandrolone can be comprehensive and evident on the blood, cardiovascular, central nervous system, musculoskeletal, gastrointestinal, renal, reproductive/endocrine and dermatological systems, as well as manifesting as psychological and behavioral effects. Therefore, the decision to use any anabolic steroid must be made with extreme caution and based on solid information, with adequate professional monitoring and a deep understanding of the possible health consequences.